A call to action - Nicholson, Tamaryn Jane (PINS-Psychology in Society, 2016)
Gqola, Pumla Dineo (2015) Rape: A South African nightmare. Auckland Park: MFBooks Joburg (Jacana Media imprint). ISBN 978-1-920601-52-2 pbk. Pages x + 192.